SOIL PROPERTIES FOR EARTH BUILDING CONSTRUCTION IN CITY OF ZAKHO-IRAQ - Adil H. Nawar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Earth is the most common and important building material used in construction industry as it found in almost every country in the world. Modern earth building is alive and well spread over an enormous geographical area using different earth materials and numerous methods of construction and has many benefits for construction and buildings. Zakho city, which is located in the south of Iraq, distinguished of its heritage earth architecture with many benefits and marvelous types and exterior views. Many weaknesses of the material, lake of knowledge and quick development caused lifting and destroying many of its mud and heritage building during the last few generations. Not all soils are suitable for every building need. Soil specification is very important to ensure that the materials used in construction meet all needs. Available locally material of common quality was taken from local site in Zakho city. Laboratory experimentation and testing was done to determine the properties of this material. Results were recorded for further studies and heritage building conversation and rehabilitation and for modern earth building material and techniques.